1 - Mokoma (yhtye); Aalto, Kuisma; Aaltonen, Miitri; Annala, Marko; Hyrkäs, Janne; Hämäläinen, Santtu; Saikkonen, Tuomo (Sakara Records, 2013)
CD-levy: 5 kappaletta.
Keywords: Mokoma (yhtye) : albumit; Mokoma (yhtye) : audiovisuaalinen aineisto